Solutions to enhance the quality of bachelor's degree training in physical education at Bac Ninh Sports University (Tạp chí khoa học Đào tạo và Huấn luyện Thể thao, 2024)
Solutions to enhance the quality of bachelor's degree training in physical education at Bac Ninh Sports University